Idiopathic facial aseptic granuloma of children. - Garofalo, L. (European Journal of Pediatric Dermatology, 2012)
Case 1. A 3-year-old child was first observed due to two asymptomatic lesions of the face, the first on the left cheek started 8 months before, in September and the second on the right cheek begun six months earlier: the lesions had reached the maximum diameter within 2 months and then had remained stationary; moreover, they had never been secreting. In his remote medical history there were recurrent catarrhal otitis and a surgical operation for preputial adhesions. The physical examination (Fig. 1, 2) revealed two nodules: the larger on the left cheek had a diameter of 12 x 8 mm, was clearly demarcated, had smooth surface, hard-elastic consistency and was not painful. The final diagnosis was idiopathic facial aseptic granuloma of children and we decide to keep it under observation without any therapy.